Machine‐Washable Textile Triboelectric Nanogenerators for Effective Human Respiratory Monitoring through Loom Weaving of Metallic Yarns. Issue 46 (30th September 2016) - Zhao, Zhizhen; Yan, Casey; Liu, Zhaoxian; Fu, Xiuli; Peng, Lian‐Mao; Hu, Youfan; Zheng, Zijian
Abstract : Textile triboelectric nanogenerators for human respiratory monitoring with machine washability are developed through loom weaving of Cu‐PET and PI‐Cu‐PET yarns. Triboelectric charges are generated at the yarn crisscross intersections to achieve a maximum short circuit current density of 15.50 mA m –2 . By integrating into a chest strap, human respiratory rate and depth can be monitored.